2008
DOI: 10.1007/s11251-008-9062-9
|View full text |Cite
|
Sign up to set email alerts
|

Self-regulated strategy development in writing: Going beyond NLEs to a more balanced approach

Abstract: In this article, we present an argument for consideration by those researching and promoting new learning environments (NLEs). We believe advocates of NLEs should consider the literature and research base indicating effective instruction is not based on a forced dichotomy between theoretical perspectives, but rather a thoughtful, pragmatic blending of practices based on evidence gained from various perspectives and lines of research. While unguided or minimally guided instructional approaches are popular and i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
27
0
7

Year Published

2009
2009
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(34 citation statements)
references
References 37 publications
0
27
0
7
Order By: Relevance
“…A constructivist stance should lead us to focus on how to best induce active sense-making and knowledge construction, irrespective whether the chosen learning environment is usually regarded as a ''traditional'' or a ''constructivist'' arrangement (cf. also the balanced position of Harris et al 2008).…”
mentioning
confidence: 88%
“…A constructivist stance should lead us to focus on how to best induce active sense-making and knowledge construction, irrespective whether the chosen learning environment is usually regarded as a ''traditional'' or a ''constructivist'' arrangement (cf. also the balanced position of Harris et al 2008).…”
mentioning
confidence: 88%
“…Several meta-analyses (Graham and Perin, 2007; Graham et al, 2012; Graham and Harris, 2014) have indicated that strategy-focused instruction is the most effective approach to improve students writing, relative to the other types on instruction identified in their meta-analyses, with typically large positive effects on the quality of students’ texts. This approach aims to give students explicit strategies for regulating both what they write and the processes that they adopt when writing it (Alexander et al, 1998; Harris et al, 2008). …”
Section: Introductionmentioning
confidence: 99%
“…Several studies have shown positive effect sizes, varying from medium to high, for the explicit teaching of specific text structure strategies that include planning and revising instruction [67,68]. The explicit teaching of those skills is needed because the difficulties students with LLD encounter in the writing process are partially due to executive control issues [20,69].…”
Section: Intervention Framework For Written Language For Students Witmentioning
confidence: 99%